New data on the deposits with "Carpathian pebbles" of the Upper Pobuzhye (the Letichev region) - Prysiazhniuk, V.A. (Reports of the National Academy of Sciences of Ukraine, 2014)
Three alluvial levels have been described for the Letichev region. The upper-level deposits attributed to the Balta suite occur at the watershed, and they are correlated with the Stolnichensko–Ananyevsk beds. In the lower-lever deposites in the Copytentsy village except Mollusksfossils, the remnants of Microthus cf. pitimis, Dicrostonix sp. and Mammuthus trogontheri are found.